Mechanical Response of Composites - Camanho, Pedro P.; Dávila, C. G.; Pinho, S. T.; Remmers, J. J. C. (Computational Methods in Applied Sciences, 2008)
This book contains twelve selected papers presented at the ECCOMAS Thematic Conference - Mechanical Response of Composites, and the papers presented by the three plenary speakers. It describes recent advances in the field of analysis models for the mechanical response of advanced composite materials, ranging from the simulation of the manufacturing process to the inelastic response and collapse of the material. The analysis models are based on recent advances in computational mechanics such as multi-scale modeling, cohesive and partition of unity models.